PENGGUNAAN KERTAS PERMANEN SEBAGAI PENCEGAHAN KERUSAKAN KERTAS - Lukman, Lukman (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2009)
The physical deterioration of library materials and archives, especially of paper based, is major professional issues of librarianship and archivists in Indonesia. The deterioration of library materials and archives must be considered since it relates to information substance and preservation concepts. In some extent, there is a consideration to use permanent paper for archrival purposes. In other hands, there has not been any special standard in Indonesian National Standard (SNI) of permanent paper for archives or reference books. Because of that, SNI of permanent paper is essential for high use value archives. This research is aimed at firstly, to identify the preparedness of user, producer and decision maker in supporting the permanent paper using for archives. Issuing SNI will be of some useful requirement to be implemented and used by them. The Indonesian National Archives (ANRI) that is responsible for establishing guidelines permanent paper for high valued archival use. Secondly, is to understand of characteristics permanent paper standard used for stakeholder. This is a qualitative descriptive research using data sources, such as regulations, related government institutions, industries, and research institutions. Data collected by interviews and observation. It found that 1). Paper industries in Indonesia are ready and able to produce permanent paper, but government institutions have not realized the importance of permanent paper uses for high use value archives. They are not aware of the Archives Decree no 4/2000 on using permanent paper for high use value archives and that permanent paper could be found in the market already. 3) Government, ANRI is ready to issue Decree related to the application of permanent paper for high use value archives. 4) Expert suggest to precise required characteristics on accelerated aging in SNI Permanent Paper, and using ISO 9706 Permanent Paper for Documents as the first step base for arranging SNI Permanent Paper.